STRATEGI MENINGKATKAN MINAT DAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL DI KELAS 8B SMP NEGRI 11 YOGYAKARTA, TAHUN AJARAN 2022/2023 MELALUI PERMAINAN KARTU - rebon, ecy; Muhammad Iqbal Birsyada; Darsono (Universitas PGRI Yogyakarta, 2023)
The research approach used by researchers in collecting data is class action research or class research. This study aims to determine student learning outcomes in social studies subjects. In learning, learning strategies are also needed so that teaching and learning objectives can be obtained in a more effective and targeted manner. In addition, the use of learning methods that are still lacking makes students less active in class. Based on the identification of students' learning activities, the enthusiasm for learning shown by students experienced an increasing trend. As for the required method that can increase student interest in learning. This can be seen from the increase in index that occurred in the first cycle and the second cycle. The application of the learning model through card games can increase the interest and learning achievement of class 8B SMP Negeri 11 Yogyakarta in learning Social Sciences. By using games, games are also able to provide space to be able to translate abstract concepts in science into simpler and easier-to-digest forms. In addition, flexibility in games is also considered important so that games can become a more varied learning medium. It is proven that from the results of observing students' activeness after applying the use of learning methods through card games the level of learning from cycle to cycle is increasing. Keywords: Achievement, Card Game, Interest and Strategy.